Low socioeconomic position is a risk factor for delay to treatment and mortality of testicular cancer patients in Hungary, a prospective study - Zsófia Küronya; Georgina Fröhlich; Andrea Ladányi; Tamás Martin; Lajos Géczi; Fruzsina Gyergyai; Orsolya Horváth; Gergő Kiszner; Ágnes Kovács; Tamás Dienes; Enikő Lénárt; Krisztián Nagyiványi; et al. (BMC, 2021)
Abstract Background In Hungary, the mortality rate for testicular germ cell cancer (TGCC) is 0,9/100000 which is significantly higher than the EU average. We prospectively evaluated the effect of socioeconomic position on patient delay and therapy outcomes. Methods Questionnaires on subjective social status (MacArthur Subjective Status Scale), objective socioeconomic position (wealth, education, and housing data), and on patient's delay were completed by newly diagnosed TGCC patients. Results Patients belonged to a relatively high socioeconomic class, a university degree was double the Hungarian average, Cancer-specific mortality in the highest social quartile was 1.56% while in the lowest social quartile 13.09% (p = 0.02). In terms of patient delay, 57.2% of deceased patients waited more than a year before seeking help, while this number for the surviving patients was 8.0% (p = 0.0000). Longer patient delay was associated with a more advanced stage in non-seminoma but not in seminoma, the correlation coefficient for non-seminoma was 0.321 (p < 0.001). For patient delay, the most important variables were the mother's and patient's education levels (r = − 0.21, p = 0.0003, and r = − 0.20, p = 0.0005), respectively. Since the patient delay was correlated with the social quartile and resulted in a more advanced stage in non-seminoma, the lower social quartile resulted in higher mortality in non-seminoma patients (p = 0.005) but not in seminoma patients (p = 0.36) where the patient delay was not associated with a more advanced stage. Conclusions Based on our result, we conclude that to improve survival, we should promote testicular cancer awareness, especially among the most deprived populations, and their health care providers.